Aging in Place: Neighborhood Attributes and the Health-related Quality of Life of Elderly People in Hong Kong - Tao, Yiqi; Fu, Jiayan; Stephen Siu Yu Lau; Shi, Shulin; Chen, Xiaowei (The journal of aging and social change, 2017)
The focus of this article is on the relationship between neighborhood environmental attributes and the health-related quality of life of 181 elderly people who live in Care and Attention (C&A) homes in Hong Kong. Objective variables of physical neighborhood attributes across nine neighborhoods (public open/green space, transport space, and service space) were measured, and subject variables were evaluated via a questionnaire and a self-rated health short form (SF-12). Correlation and logistic regression models were used for data analysis. A positive relationship was found between respondents’ satisfaction level and the provision of public open/green spaces, transport space, and public toilets. The provision of public open/green space and transport space around C&A homes was found to benefit the physical health of the respondents, and the provision of service space, such as convenience stores and public toilets, influenced their mental health. Local authorities responsible for high-density urban neighbourhoods should make better provisions for elderly residents by monitoring the variables discussed in this article.